2020
DOI: 10.9734/cjast/2020/v39i2030815
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Divergence Studies for Gall Midge Incidence, Earliness, Yield and Yield Components in Rice (Oryza sativa L.) Genotypes in Telangana State

Abstract: The study was carried out with 32 genotypes of rice (Oryza sativa L.) under irrigated system in RBD design with three replications at Agricultural Research Station, Kunaram in Telangana State during the rainy season of 2017. In general, major problem is high incidence of gall midge (Biotype 3) in rainy season under early as well as late planting conditions in Northern Zone of Telangana State. Hence, all the 32 genotypes were evaluated with an aim to know the divergence among them for gall midge incidence, earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
4
2
0
Order By: Relevance
“…Low estimates of both parameters were found for hulling percentage indicating that non-additive genes may play a role in the inheritance of this trait and that breeding for heterosis or recurrent selection is preferable in order to improve such kind of trait. These results are in accordance with the findings of Srinivas et al [30] and Sreedhar Siddi and Anil Deva [20].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Low estimates of both parameters were found for hulling percentage indicating that non-additive genes may play a role in the inheritance of this trait and that breeding for heterosis or recurrent selection is preferable in order to improve such kind of trait. These results are in accordance with the findings of Srinivas et al [30] and Sreedhar Siddi and Anil Deva [20].…”
Section: Resultssupporting
confidence: 93%
“…The mean performance of parents, crosses, and checks recorded on 14 characters is presented in Phenotypic and genotypic coefficient of variations (Table 4) showed that PCV values were higher than GCV values for all the traits indicating that environmental factors play a role in how these traits are expressed. The results of this study provided confirmation with Toshimenla and Changkija [14], Vanisree et al [15], Tuhina et al [16], Savitha and Usha Kumari [17], Bhinda et al [18], Siddi et al [19], Sreedhar Siddi and Anil Deva [20], Srinivas et al [21] and Subhas Chandra Roy and Pankaj Shil [22]. The GCV was found to be less than PCV for all the traits except for the number of productive tillers per plant.…”
Section: Resultssupporting
confidence: 86%
“…It might be due to their different genetic makeup from that of other germplasm lines in the present study. Similar results of greater genetic diversity for the genotypes in the monogenotypic clusters were also reported by Prasad et al (2021), Raju et al (2021), Siddi (2020), Srinivas et al (2016) and Mohan et al (2015).…”
Section: Resultssupporting
confidence: 87%
“…These genotypes may be used for developing early and medium duration genotypes. Moreover, it was interesting to note that in most of the cases, cluster VII produced the highest inter cluster value with all other (Siddi, 2020).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation